2017
DOI: 10.1515/bjmg-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of hemostatic factors and thrombotic risk in non BCR-ABL myeloproliferative neoplasms: A pilot study

Abstract: The most important complications of Philadelphianegagive (non BCR-ABL) myeloproliferative neoplasms (MPNs) are vascular events. Our aim was to evaluate the effects of single nucleotide polymorphisms (SNPs), platelet glycoproteins (GPs) (Ia/IIa, Ibα, IIb/IIIa and VI), von Willebrand factor (vWF), coagulation factor VII (FVII), β-fibrinogen, and the risk of thrombosis in patients with non BCR-ABL MPNs at the Lithuanian University of Health Sciences. Kaunas, Lithuania. Genotyping was done for 108 patients. The TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, HPA-1a/1b GPIIIa variant failed to show any thrombosis correlation between PV and ET patients [149]. Study on another GPIa/IIa c.807C > T polymorphism [150], MPN patients with arterial thrombosis exhibited a higher frequency of TT genotype (26.5 vs. 11.5%, p = 0.049; odds ratio 2.68). Genetic predisposition may be stacked up in patients with MPN when SNPs affecting DNA repair and apoptosis are present.…”
Section: Gene Polymorphisms In Thrombotic Mpnmentioning
confidence: 99%
See 2 more Smart Citations
“…However, HPA-1a/1b GPIIIa variant failed to show any thrombosis correlation between PV and ET patients [149]. Study on another GPIa/IIa c.807C > T polymorphism [150], MPN patients with arterial thrombosis exhibited a higher frequency of TT genotype (26.5 vs. 11.5%, p = 0.049; odds ratio 2.68). Genetic predisposition may be stacked up in patients with MPN when SNPs affecting DNA repair and apoptosis are present.…”
Section: Gene Polymorphisms In Thrombotic Mpnmentioning
confidence: 99%
“…Another gene polymorphisms within the β-fibrinogen (FBG), the heterozygous CT genotype of FBG c.-148C > T polymorphism is crucially higher (p = 0.02) in MPN patients with thrombotic events (57.7%) than CC wild type (40.0%) or TT homozygous (12.5%), but not for −455G/A FBG polymorphism [149]. Moreover, the presence of polymorphism in clotting factor II (F2) or G20210A mutation of prothrombin and clotting factor V (F5) or Leiden mutation has no significant association with thrombosis in patients with PV and ET [150,152]. A different outcome was obtained from another study [153], which found no difference between F5 mutation and arterial thrombosis (p = 0.337), but a higher rate of detection of venous thrombosis before and at time of diagnosis and recurrence of venous thrombosis in patients with PV and ET (p = 0.03).…”
Section: Gene Polymorphisms In Thrombotic Mpnmentioning
confidence: 99%
See 1 more Smart Citation
“…Myeloproliferative neoplasms (MPNs), by definition, are clonal hematologic diseases that occur by overproduction of active blood cells [1]. The group of Philadelphia-negative (Ph-, non BCR-ABL) myeloproliferative neoplasms, polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF), are known for their different phenotypes but similar complications [2]. Primary myelofibrosis specifically is a clonal stem cell disorder that is characterized by chronic myeloproliferation, megakaryocytic hyperplasia and the presence of the myeloid series immature cells in the circulating blood [3].…”
Section: Introductionmentioning
confidence: 99%